2015
DOI: 10.1007/s00180-015-0627-1
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian estimation of bandwidth in semiparametric kernel estimation of unknown probability mass and regression functions of count data

Abstract: This work takes advantage of semiparametric modelling which improves significantly in many situations the estimation accuracy of the purely nonparametric approach. Herein for semiparametric estimations of probability mass function (pmf) of count data, and an unknown count regression function (crf), the kernel used is a binomial one and the bandiwdth selection is investigated by developing Bayesian approaches. About the latter, Bayes local and global bandwidth approaches are used to establish data-driven select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…However, in this paper and following Senga Kiessé et al (2015) and, Zougab et al (2014) we choose α = 0.5 and β = √ n. The choice of β which depends on the sample size n is important for the consistency of nonparametric kernel estimator of pmf and permits the convergence of Bayesian bandwidths estimators to zero (h j → 0 while n → ∞ for j = 1, . .…”
Section: Q(h (T)mentioning
confidence: 98%
See 1 more Smart Citation
“…However, in this paper and following Senga Kiessé et al (2015) and, Zougab et al (2014) we choose α = 0.5 and β = √ n. The choice of β which depends on the sample size n is important for the consistency of nonparametric kernel estimator of pmf and permits the convergence of Bayesian bandwidths estimators to zero (h j → 0 while n → ∞ for j = 1, . .…”
Section: Q(h (T)mentioning
confidence: 98%
“…Therefore, recently the so-called discrete associated kernel method is largely developed by several authors; see, e.g., Kokonendji and Senga Kiessé (2011), Kokonendji, Senga Kiessé, and Balakrishnan (2009), Kokonendji et al (2007), Wansouwé, Kokonendji, and Kolyang (2015), Zougab, Adjabi, and Kokonendji (2012) and Zougab, Adjabi, and Kokonendji (2013a). Note that the semi-parametric estimation of pmf and count rf (crf) is also investigated, see for example Abdous, Kokonendji, and Senga Kiessé (2012) and Senga Kiessé, Zougab, and Kokonendji (2015). They showed that the use of a discrete associated kernel is more appropriate than the use of a continuous kernel for both estimations of pmf and crf of a discrete variable.…”
Section: Introductionmentioning
confidence: 98%
“…However, the naive estimator is appropriate only when the sample size is large, and the discrete kernel of Aitchison and Aitken (1976) is only suitable for categorical data; see Hayfield and Racine (2008) and also Hayfield and Racine (2014). Kokonendji et al (2009) adapted the Nadaraya (1964) and Watson (1964) kernel to the discrete unknown function m, using the discrete associated kernels. In their work, using the integrated mean square error and the coefficient of determination R 2 , they showed that the binomial or discrete triangular kernels are better compared to the optimal Epanechnikov kernel.…”
Section: Bandwidth Selection For Kernel Regression Involving Associatmentioning
confidence: 99%
“…where m −i (X i ) is computed as m n of (24) excluding X i ; see, e.g., Kokonendji et al (2009). The hcvreg.fun function to compute this optimal bandwidth is described in Table 3.…”
Section: Cross-validation For Any Associated Kernelmentioning
confidence: 99%
“…f of 1 i.i.d. observations (X i ) i=1,••• ,n was constructed to behave asymptotically as the frequency estimator F(x) = n −1 n i=1 1 {x} (X i ), x ∈ S, where 1 A denotes the indicator function of the set A (for details about f , see later equation (6) in Section 3).…”
Section: Introductionmentioning
confidence: 99%